1999
DOI: 10.1159/000006958
|View full text |Cite
|
Sign up to set email alerts
|

Pain Recollection after Chest Pain of Cardiac Origin

Abstract: Memory for pain is an important research and clinical issue since patients ability to accurately recall pain plays a prominent role in medical practice. The purpose of this prospective study was to find out if patients, with an episode of chest pain due to suspected acute myocardial infarction could accurately retrieve the pain initially experienced at home and during the first day of hospitalization after 6 months. A total of 177 patients were included in this analysis. The patients rated their experience of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 12 publications
(20 reference statements)
3
37
0
1
Order By: Relevance
“…Other studies that have assessed patients' ability to recall pain, functional status, and general health have had mixed results [20e38] although differences between studies in their design may help to explain these inconsistencies. For example, some studies asked patients to recall specific experiences (e.g., worst pain, least pain) [20,22,23,26,28,38], whereas others asked patients to recall their average experience (e.g., average pain over the past week) [29,31]. Patients were unable to accurately recall specific experiences but showed good recall of average experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that have assessed patients' ability to recall pain, functional status, and general health have had mixed results [20e38] although differences between studies in their design may help to explain these inconsistencies. For example, some studies asked patients to recall specific experiences (e.g., worst pain, least pain) [20,22,23,26,28,38], whereas others asked patients to recall their average experience (e.g., average pain over the past week) [29,31]. Patients were unable to accurately recall specific experiences but showed good recall of average experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that asked patients to recall over a longer timeframe (2 months to 10 years) [21,23,25,26,28,37,38] found that patients could not recall their pretreatment status accurately, whereas studies that asked patients to recall over a shorter timeframe (1 day to 2 weeks) [24,29,31,33] found that patients could provide accurate ratings of pain and function. In our study, patients were asked to recall preoperative quality of life, general health, and functional status at an average of 2 weeks following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Significant associations between numerical ratings of pain have been taken to suggest that its intensity or severity can be recalled quite accurately. 6,7,22 On the other hand, studies that have assessed memory for qualitative dimensions of pain have been more equivocal in their findings. 1,3,6,12,19,21,26 The issue of assessing memory for pain is also complicated by the fact that a number of similarities have been observed between reports of an actual pain event, made by those who have experienced it, and estimates made by those with no personal experience of the pain.…”
mentioning
confidence: 99%
“…Collectively, it appears that acute pain experiences are accurately recalled during a period of weeks, 23,38 however, recollection is generally exaggerated when the period of recall extends into months. 15,25 Investigation of the role of negative emotion in acute pain memory processing is in its infancy, however, evidence suggests a positive and meaningful association. 14,15,18,23,25 For example, Everts et al 15 contacted patients 6 months after treatment for acute myocardial infarct and requested them to recall their level of pain at the time of treatment.…”
mentioning
confidence: 99%